Reevaluating Risk and Responsibility: Broader Implications of Construction Contract Regulations in Indonesia and Globally - Yossica Ariatami Edwina; Putra Alfa Rizki; Varun Chhachhar; Phuvadech Rasamichai (Journal of Private and Commercial Law, 2025)
This article critically examines the evolving landscape of risk and responsibility in construction contract regulations, with a focus on Indonesia and broader global contexts. A construction project is inherently subject to various risks, which increase in proportion to the project's complexity. Discrepancies between planning and actual conditions often lead to unforeseen risks, placing significant responsibility on all parties involved. In Indonesia, regulatory frameworks such as the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata) and the Construction Law (Undang-Undang No. 2/2017) provide some guidance, but ambiguities surrounding risk management and contractor responsibility persist, often resulting in disputes, project delays, and inefficiencies. This research, using a normative juridical method with a statute approach, critically explores the division of risk burden (risk sharing) and the responsibilities of parties in construction contracts under both Indonesian laws and the guidelines of the International Federation of Consulting Engineers (FIDIC). The study also reviews risk allocation practices in other jurisdictions, such as the European Union, the United States, and the United Kingdom, to provide insights into varying approaches to risk management. The results indicate that parties involved in construction projects share an implicit obligation to collaborate in minimizing the negative consequences of unforeseen events. By categorizing risks according to their sources and types, a fair, balanced, and equitable risk-sharing framework can be achieved. This paper proposes the need for a redefined regulatory framework in Indonesia that integrates transparent accountability measures and collaborative risk management strategies, contributing to a more sustainable and efficient construction environment both domestically and globally.